2021
DOI: 10.1177/00031348211048834
|View full text |Cite
|
Sign up to set email alerts
|

Trampoline Injuries in a Statewide Trauma System

Abstract: Introduction It is well known that trampolines can be a particular source of danger, especially in children. We sought to examine the profile of those patients with trampoline injuries. We hypothesized there would be certain injury patterns predicative of trampoline injuries. Methods All patients submitted to Pennsylvania Trauma Outcome Study database from 2016 to 2018 were analyzed. Trampoline injury was determined by ICD-10 activity code. Injury patterns in the form of abbreviated injury scale body regions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…[8][9][10][11] A recent statewide study has reported head injuries to be 4.76% of all trampoline-related injuries. 12 Nevertheless, there have been no studies in the literature to date that specifically investigated head and neck injuries secondary to trampoline use. Trampoline-related injuries to the neck that have been reported are limited to case reports and series.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] A recent statewide study has reported head injuries to be 4.76% of all trampoline-related injuries. 12 Nevertheless, there have been no studies in the literature to date that specifically investigated head and neck injuries secondary to trampoline use. Trampoline-related injuries to the neck that have been reported are limited to case reports and series.…”
Section: Introductionmentioning
confidence: 99%
“…6,12,15,25,29 A recent study reported an incidence of lower extremity injuries of 34% among all trampoline injuries, without discriminating specific injury characteristics or anatomic regions such as ankle, knee, or hip. 29…”
Section: Discussionmentioning
confidence: 99%
“…Trampolinerelated injuries were studied in Asia, Australia, France, and Austria, reporting similar trends in injury presentation, with extremity injuries being the most prevalent. 6,12,15,25,29 A recent study reported an incidence of lower extremity injuries of 34% among all trampoline injuries, without discriminating specific injury characteristics or anatomic regions such as ankle, knee, or hip. 29 In this study, most injuries among skeletally mature patients were sustained in trampoline parks, while skeletally immature patients were most often injured on backyard trampolines.…”
Section: The Orthopaedic Journal Of Sports Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…The rise of recreational activities and sports in the household environment has also created unique events leading to spine injuries [ 7 ]. Trampoline use has accounted for a substantial proportion of spine injuries in children and adolescents, emphasizing the need for safety guidelines and adult supervision while using trampolines [ 16 ]. Similarly, the widespread adoption of electronic devices has increased spine injuries related to their use at home.…”
Section: Introductionmentioning
confidence: 99%